Dirasah Sikulujiyah Adabiyah Sigmund Freud Fi Syakhshiyah “Samiyah” Fi Masrahiyah Qitath wa Firan Li Ali Ahmad Bakatsir - M Romadhoni (Journal of Arabic Literature (JaLi), 2020)
This study aims to determine the form and causes of the characterization of the character "Samiyah" in the drama "Kucing and Tikus". Using descriptive qualitative methods through a literary psychology approach, this study consider the data in the form of words in the conversational quotes from the drama "Kucing and Tikus". The results of the Freudian personality-psychoanalysis theory show that samiyah is more dominant in the ego which is her natural character from id such as emotional, materialism, riya and ambitious. Superego has regulated or controled attitude and behavior, namely hardworking, obedient, fair, and not easily get provoked.